Folk time [compact disc] - Garcia, Jerry, 1942-1995 (Jerry Garcia Family LLC ; Round Records ; ATO Records, 2016)
The Hart Valley Drifters was one in the long line of groups Jerry Garcia put together during the folk revival of the early '60s, but it was perhaps his first band to present a professional level of musicianship and vocal harmony. This release, a previously unheard studio recording of Garcia at age twenty, fills in a nearly empty slot of his musical canon, and is the earliest known studio recording of him.